2008
DOI: 10.1016/j.neuron.2008.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Social and Monetary Rewards in the Human Striatum

Abstract: Despite an increasing focus on the neural basis of human decision making in neuroscience, relatively little attention has been paid to decision making in social settings. Moreover, although human social decision making has been explored in a social psychology context, few neural explanations for the observed findings have been considered. To bridge this gap and improve models of human social decision making, we investigated whether acquiring a good reputation, which is an important incentive in human social be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

55
638
6
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 744 publications
(701 citation statements)
references
References 73 publications
55
638
6
2
Order By: Relevance
“…Our previous finding of activation in ventral striatum during judgments of self and a close other (Grigg & Grady, 2010a) is consistent with the idea that there is an intimate link between self and reward (Northoff & Hayes, 2011). Others have shown that social stimuli, such as faces, can have rewarding properties and activate the ventral striatum (Izuma, Saito, & Sadato, 2008;Liang, Zebrowitz, & Zhang, 2010), and that learning about social information involves the same kinds of behavioral processes, and some of the same brain areas, as learning about the rewarding properties of stimuli (Behrens, Hunt, Woolrich, & Rushworth, 2008).…”
Section: The Reward Network (Rn)supporting
confidence: 88%
“…Our previous finding of activation in ventral striatum during judgments of self and a close other (Grigg & Grady, 2010a) is consistent with the idea that there is an intimate link between self and reward (Northoff & Hayes, 2011). Others have shown that social stimuli, such as faces, can have rewarding properties and activate the ventral striatum (Izuma, Saito, & Sadato, 2008;Liang, Zebrowitz, & Zhang, 2010), and that learning about social information involves the same kinds of behavioral processes, and some of the same brain areas, as learning about the rewarding properties of stimuli (Behrens, Hunt, Woolrich, & Rushworth, 2008).…”
Section: The Reward Network (Rn)supporting
confidence: 88%
“…Based on the role of these regions in reward processing [Carlson et al, 2011;Cromwell et al, 2005;McClure et al, 2004;Rushworth et al, 2011;Sescousse et al, 2015], our findings dovetail with the notion that downward comparison is experienced as rewarding [Bault et al, 2011;Dvash et al, 2010;Fliessbach et al, 2007]. Prior studies have shown the involvement of the VS in the processing of other types of social rewards, including good reputation [Izuma et al, 2008;Meshi et al, 2013] and social approval [Izuma et al, 2010]. These findings have led researchers to propose that the VS and vmPFC, in addition to being key brain areas for material reward (e.g., food and money) processing, also play a crucial role in registering a broad spectrum of social rewards [Delgado, 2007].…”
Section: Discussionsupporting
confidence: 85%
“…Error bars reflect one between-subject SE. Social learning of value is modulated by methylphenidate DK Campbell-Meiklejohn et al findings that agreement with others and gains of reputation evoke similar reward activity in the striatum to that of nonsocial rewards (Campbell-Meiklejohn et al, 2010;Izuma et al, 2008;Zink et al, 2008). The hypothesis also assumes that the magnitude of a cued incentive is carried by phasic dopamine signals, which has been shown previously (Tobler et al, 2005).…”
Section: Discussionmentioning
confidence: 91%
“…Correspondingly, studies have consistently reported that cognitive components of conformity can be tracked in the activity of brain regions known to mediate reinforcement learning. These include responses to social agreement (Campbell-Meiklejohn et al, 2010), conformity-inducing conflict (Berns et al, 2010;Campbell-Meiklejohn et al, 2010;Klucharev et al, 2009), changes of reputation (Izuma et al, 2008;Zink et al, 2008), and socially induced changes of object value (CampbellMeiklejohn et al, 2010;Mason et al, 2009;Zaki et al, 2011). In nonsocial domains, task performance related to the same fronto-striatal circuitry is known to be sensitive to levels of catecholamine activity (Berridge, 2007;Clatworthy et al, 2009;Cools et al, 2001;Del Campo et al, 2011;Robbins and Arnsten, 2009), but catecholamine mediation of conformity of value has not yet been established.…”
Section: Introductionmentioning
confidence: 99%